Pseudothrombocytopenia in Asymptomatic Outdoor Patients Presenting with Low Platelet Counts - Farid, Jamila (International Journal of Pathology, 2019)
Background: Pseudothrombocytopenia is spuriously low platelet count seen in complete blood count performed on an automated hematology analyzer. It may lead to unnecessary investigations& management. It has been postulated to be caused by an anticoagulant namely Ethylene-Diamine-Tetra Acetic-Acid (EDTA)and has been reported in physiological as well as disease conditions with variable frequency. No significant research has been done on this important clinical entity in our country. Objective: To see the prevalence of pseudothrombocytopenia in our settings. Methods: EDTA based hematology analyzer method was used as the initial test for blood counts. Patients showing thrombocytopenia were screened for pseudothrombocytopenia by giemsa stained blood film examination. Those with platelet aggregates were labeled as pseudothrombocytopenia and were studied further by doing manual platelet count (ammonium oxalate method) and repeat automated platelet count on a citrate based fresh blood sample. Manual platelet count was also performed on blood samples not showing platelet aggregates, as a second security check, after which, those with low platelet count were labeled as true asymptomatic thrombocytopenia. Results: Out of 385 patients, 30 revealed pseudothrombocytopenia, Eight patients were male and 22 females, female to male ratio was 2.75:1. Ten patients were less than twenty five years old; 15 patients were 25 to 50 years and five patients aged more than 50 years. Mean age of the patients was 32.7±16.5 years. Machine generated blood report using EDTA blood, revealed platelet count <50 ×103/µl in 16(53.4%), 40-100×103/µl in 12(40%) & 100-149×103/µl in 2 (6.7%) patients respectively. Mean platelet count was 50±25×103/µl l . No patient had platelet count of >150×103 /µl by this method. Platelet count using sodium citrate revealed platelets >150 ×103 /µl in 25(83.4%) and 100-149×103/µl in 5(16.6%) patients. By manual method none of patients had platelets lower than 150 ×103/µl. Conclusion: Pseudothrombocytopenia is more common in females, when EDTA is used as anticoagulant and is seen in all age groups.